Anthropology with an attitude : critical essays - Fabian, Johannes (Stanford, Calif. : Stanford University Press, 2001)
Prelude: With So Much Critique and Reflection Around, Who Needs Theory? ## Critical Concerns ## Ethnographic Objectivity: From Rigor to Vigor ## Ethnographic Misunderstanding and the Perils of Context ## Keep Listening: Ethnography and Reading ## Ethnology and History ## Culture with an Attitude ## Critical Memories ## Hindsight ## Curios and Curiosity ## Time, Narration, and the Exploration of Central Africa ## Remembering the Other: Knowledge and Recognition ## Africa's Belgium ## Coda: Not in a Thousand Years: On the (Ir)relevance of the Millennium.
Includes bibliographical references and index.
boek